Laku Tasawuf sebagai Terapi Psikospiritual - Dikhorir Afnan (JIKE: Jurnal Ilmu Komunikasi Efek, 2018)
ABSTRACT Human existence is built on the consciousness of two things as transcendent creatures (transcendere), and as immanent beings (Latin: immanere, abiding within). Man makes himself, with all activities and the result builds his own uniqueness (Syam, 2015). One of the traditions and culture of Javanese society in the spiritual context is the behavior of Sufism. The research was conducted to trace the ritual of worship as transedental creature in group of jamaah "Ilmu Sejati" in Karangampel Village of Indramayu Regency. In this study, researchers used qualitative descriptive methodology. The results of this study include: Sufism behavior as psychospiritual therapy in the congregation "True Science" includes congregational prayers, munajat, khalwat and tirakat. (1) The worship ritual of worship congregation becomes a daily portrait of the congregation of "Real Science". At certain moments, the month of Ramadan for example, in addition to the obligatory prayers 5 times and tarawih prayers, all pilgrims are encouraged to perform salat sunah hajat and tahajud one full month. (2) Munajat is the core of the teachings of "Real Science". Bermunajat or berzikir is a process to Allah SWT. To be able to "get" to communicate with Him, they first purify themselves, both physically and mentally. (3) The practice of khalwat on the teachings of "Real Science" is only done by the highest leadership, namely Ibn Salma bin Kadar Yahya. This procession of self-isolation he did during the early establishment of the teachings of "Real Science" around 1997. (4) Tirakat or fasting on the teachings of "Real Science" also can only be done by Ibn Salma as the leader of the pilgrims. The behavior of tirakat can be referred to as a complementary ritual of the teachings of "True Science" besides the ritual of the play. Keywords: Transcendental Communication, Sufism, Religious Psychology